Ionizing Radiation Induces Endothelial Inflammation and Apoptosis via p90RSK-Mediated ERK5 S496 Phosphorylation - Vu, Hang Thi; Kotla, Sivareddy; Ko, Kyung Ae; Fujii, Yuka; Tao, Yunting; Medina, Jan; Thomas, Tamlyn; Hada, Megumi; Sood, Anil K.; Singh, Pankaj Kumar; Milgrom, Sarah A.; Krishnan, Sunil; et al. (Frontiers in Cardiovascular Medicine, 2018)
Background: Adverse cardiovascular events are a leading nonmalignant cause of morbidity and mortality among cancer survivors who have been exposed to ionizing radiation (IR), but the exact mechanism of the cardiovascular complications induced by IR remains unclear. In this study we investigated the potential role of the p90RSK-ERK5 module in regulating IR-induced endothelial cell inflammation and apoptosis. Methods and Results: Whole body radiation of mice with 2 Gy γ-ray significantly increased endothelial VCAM-1 expression; especially in the disturbed flow area in vivo. In vitro studies showed that IR increased p90RSK activation as well as subsequent ERK5 S496 phosphorylation in cultured human endothelial cells (ECs). A specific p90RSK inhibitor, FMK-MEA, significantly inhibited both p90RSK activation and ERK5 S496 phosphorylation, but it had no effect on IR-induced ERK5 TEY motif phosphorylation, suggesting that p90RSK regulates ERK5 transcriptional activity, but not its kinase activity. In fact, we found that IR-induced NF-kB activation and VCAM-1 expression in ECs were significantly inhibited by the over-expression of S496 phosphorylation site mutant of ERK5 (ERK5 S496A) compared to overexpression of wild type ERK5. Furthermore, when ECs were exposed to IR, the number of annexin V positive cells increased, and overexpression of ERK5 S496A, but not wild type ERK5, significantly inhibited this increase. Conclusions: Our results demonstrate that IR augmented disturbed flow-induced VCAM-1 expression in vivo. Endothelial p90RSK was robustly activated by IR and subsequently up-regulated ERK5 S496 phosphorylation, inflammation, and apoptosis in ECs. The EC p90RSK-ERK5 signaling axis can be a good target to prevent cardiovascular events after radiation therapy in cancer patients.